Merkwürdig oder nicht? What Economic Voting Models and the 2013 Bundestag Elections Have to Say about Each Other. Issue 1 (2nd January 2017) - Seki, Katsunori; Whitten, Guy D.
Abstract : The 2013 Bundestag elections took place at a time when public opinion was strongly focused on a wide range of economic issues. But, given the coalition government and the complex array of policymakers whose hands were on the wheels of the German economy, some economic voting models would predict that the economy would play little role in deciding these elections. In this article, we use a mixture of aggregate and survey data to test what a range of different economic voting models predicted about the 2013 Bundestag elections and the extent to which these predictions were supported. The results from this exercise provide insights not only about the nature of the 2013 elections, but also about the applicability and adaptability of economic voting models to different political and economic circumstances.